Notes on the Theory of Inflation - Simkin, C. G. F. (Review of Economic Studies, 1952)
Journal Article Notes on the Theory of Inflation Get access C. G. F. Simkin C. G. F. Simkin Auckland, New Zealand Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 20, Issue 2, 1952, Pages 143–151, https://doi.org/10.2307/2295848 Published: 01 January 1952